PENGARUH VIDEO PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR PAI SISWA SMP SEPULUH NOVEMBER SIDOARJO - Mayangsari Nikmatur Rahmi; Mazidatul Rohmah; Luluk Wulandari (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
Teacher skills in obtaining student learning outcomes are something that needs more attention, because the form of student learning outcomes is a form of teacher success in teaching. Teachers can have their own assessments for themselves and know their teaching skills. Therefore, the learning video media here is a form of interactive media to determine student learning outcomes. The purpose of this study was to determine whether interactive learning video media had an effect on student learning outcomes. The results of this study indicate that the significance value of the data before and after using interactive video video media on student learning outcomes is 0.000 <0.05 which indicates that interactive learning video media have a significant effect on student learning outcomes.